Substituição da farinha de peixe pela silagem de peixe na alimentação de girinos de rã-touro (Rana catesbeiana) - Secco, Edney Murillo [UNESP]; Stéfani, Marta Verardino De [UNESP]; Vidotti, Rose Meire [UNESP] (Universidade Federal de Santa Maria, 2002)
The present work aimed at evaluating the effects of replacement of fish silage on the bullfrog tadpoles diet. A total of five diets was tested as follows: D0- 100% fish meal (FM); D1- 50% FM and 50% acid silage obtained from tilapia filleting residue (AFR); D2- 100% AFR; D3- 50% FM and 50% acid silage obtained from whole freshwater fish (AFF) and D4- 100% AFF. All treatments were carried with four replicates and a completely randomized design. The parameters analyzed for both performance and body composition of the tadpoles showed that the best results were obtained with diets D0 , D1, and D3. The results did not differ statistically among themselves, which indicates that fish meal can be replaced, up to 50%, by acid silage from tilapia filleting residue or whole freshwater fish.

O presente trabalho teve como objetivo avaliar o efeito da substituição da farinha de peixe por diferentes tipos de silagens de peixe na alimentação de girinos de rã-touro. Foram testadas cinco dietas experimentais: D0-100% de farinha de peixe (FP); D1-50% FP e 50% silagem ácida de resíduo da filetagem de tilápia (RTA); D2-100% RTA; D3- 50% FP e 50% silagem ácida de descarte de peixe inteiro de água doce (ADA) e D4-100% ADA, com quatro repetições por tratamento num delineamento inteiramente casualizado. Os parâmetros analisados, tanto para desempenho dos girinos como para composição corporal, indicaram que os melhores resultados foram obtidos quando os girinos receberam as dietas D0, D1 ou D3, as quais não diferiram estatisticamente entre si. Estes resultados indicam que a farinha de peixe em dietas para girinos pode ser substituída em até 50% por silagem ácida de resíduo da filetagem de tilápia como por silagem ácida de descarte de peixe inteiro de água doce.
Replacement of fish meal by fish silage on bullfrog tadpoles (Rana catesbeiana) feeding
Keywords: fish silage; bullfrog tadpoles; Rana catesbeiana; silagem de peixe; girinos de rã-touro; Rana catesbeiana